PEMBELAJARAN TEMATIK TERPADU BERBASIS PENDEKATAN SAINTIFIK DI TAMAN KANAK-KANAK - SURYANA, DADAN (Jurnal Pendidikan Usia Dini, 2017)
This study aims to achieve the ability to observe, ask, try, reason, and communicate through the development of the themes that have been implemented. The learning process experienced by children in an effort to discovery learning. The process of developing the ability to think this is a process of discovery learning as meaningful learning. This meaningful learning required by younger children as a learning process that will be the foundation of knowledge in dealing with the stage of development thinking that will ultimately provide a solid foundation in the face of continued education stage. The process of learning through scientific approach is very appropriate if delivered through an integrated thematic approach. Thematic learning integrated is learning that can instill the basic concepts of knowledge, to increase knowledge of facts, and can provide an interesting learning because the theme is deliver that is very close to the child, simple, attractive, and incidental (according to the event is happening) , This study uses a method research and development of Borg & Gall with six (6) steps of development. Through ten steps of this development will provide easy steps to serve as the research methods of thematic development of teaching materials based integrated scientific approach in kindergarten in West Sumatra. Keywords: Thematic, scientific, early childhood